Medical Humanitarianism: Anthropologists Speak Out on Policy and Practice. (23rd October 2014) - Abramowitz, Sharon; Marten, Meredith; Panter‐Brick, Catherine
Abstract : In recent years, anthropologists have become increasingly present in medical humanitarian situations as scholars, consultants, and humanitarian practitioners and have acquired insight into medical humanitarian policy and practice. In 2012, we implemented a poll on anthropology, health, and humanitarian practice in which 75 anthropologists discussed their experiences in medical humanitarianism. Our goal was to move beyond the existing anarchy of individual voices in anthropological writing and gain an aggregate view of the perspective of anthropologists working in medical humanitarian contexts. Responses lead to six inductively derived thematic priorities. The findings illustrate how anthropologists perceive medical humanitarian practice; which aspects of medical humanitarianism should be seen as priorities for anthropological research; and how anthropologists use ethnography in humanitarian contexts.